2012
DOI: 10.1007/s00380-012-0247-4
|View full text |Cite
|
Sign up to set email alerts
|

Endomyocardial biopsy in a patient with hemorrhagic pheochromocytoma presenting as inverted Takotsubo cardiomyopathy

Abstract: A 29-year-old female patient presented with shock and dyspnea due to heart failure and pulmonary edema. Echocardiography indicated excessive contraction limited to the left ventricular apex and akinesis of the basal and middle ventricle, which were confirmed by emergency left ventriculography. The finding was diagnostic of inverted Takotsubo cardiomyopathy. An abdominal computed tomography scan showed a tumor in the left adrenal gland with a central low-density area, and the plasma and urinary catecholamines w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 31 publications
2
14
0
Order By: Relevance
“…These findings are compatible with the clinical course. There are only two reports of the endomyocardial biopsy findings in patients who were diagnosed with catecholamine-induced cardiomyopathy and pheochromocytoma; both of whom recovered after treatment (10,11). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are compatible with the clinical course. There are only two reports of the endomyocardial biopsy findings in patients who were diagnosed with catecholamine-induced cardiomyopathy and pheochromocytoma; both of whom recovered after treatment (10,11). …”
Section: Discussionmentioning
confidence: 99%
“…Iio et al (10) demonstrated neutrophilic infiltration and diffuse contraction-band necrosis in a myocardial biopsy specimen that was taken on admission in a patient with cardiogenic shock due to pheochromocytoma and inverted Takotsubo cardiomyopathy-like wall motion of the LV. In their case, the neutrophilic infiltration that occurred in association with contraction band necrosis might have been related to the acute phase or to the administration of catecholamine, which is used to treat cardiogenic shock in patients with severe catecholamine-induced cardiomyopathy and pheochromocytoma.…”
Section: Discussionmentioning
confidence: 99%
“…Some case reports have also indicated that a pheochromocytoma can induce cardiomyopathy with a reverse takotsubo contractile pattern (3,(8)(9)(10)(11). Reverse takotsubo cardiomyopathy has been reported as an LV dysfunction in which the basal and mid-ventricular segments are hypokinetic al- though the apex appears normal.…”
Section: Discussionmentioning
confidence: 99%
“…However, in addition to excessive circulating catecholamines, substantial local release of norepinephrine occurs from myocardial nerve endings following neurologic injury (25). Aside from SAH, reversible LV dysfunction has been described in other situations where catecholamines are clearly elevated, such as in the setting of a pheochromocytoma (27). Sympathectomy, but not adrenalectomy, prevents cardiac dysfunction in animal studies of SAH, further supporting the role of local catecholamines in the pathogenesis of this disease (26).…”
Section: Pathophysiologymentioning
confidence: 98%
“…Structural cardiac changes have been described in patients with significant neurologic injury as well as in other states of excessive catecholamine release, including pheochromocytoma and tetanus (27,28,34,35). These changes are consistently described as focal myocytolysis or myofibrillary degeneration, also termed "contraction band necrosis."…”
Section: Pathophysiologymentioning
confidence: 99%